2021
DOI: 10.3390/ma14133674
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Durability and Strength Parameters of Pumice Based Mixtures

Abstract: The numerical modelling of chloride penetration into concrete is very sensitive to the correct description of the input data. In the recent era, high-performance concrete (HPC), which combines Portland cement and other supplementary cementitious materials, has been gaining attraction due to their desirable material properties and durability. The presented results show the application of the modified approach for the evaluation of the suitability of the time-dependent model for the variation of the diffusion co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Pumice concrete is widely used in current civil construction, making it more economical and reasonable for people, but the use of pumice concrete in a large area needs theoretical support and practical verification. Its engineering application value is that it can be added to concrete to play a skeleton role, which is widely used in the production of pumice lightweight aggregate concrete (PLAC) [1]. When the pre-wet pumice replaces the coarse aggregate by 30~40%, the PLAC processed has the advantages of low density, good compressive strength, split tensile strength, and flexural strength, which obviously improves the dynamic performance of the interfacial transition zone (ITZ) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Pumice concrete is widely used in current civil construction, making it more economical and reasonable for people, but the use of pumice concrete in a large area needs theoretical support and practical verification. Its engineering application value is that it can be added to concrete to play a skeleton role, which is widely used in the production of pumice lightweight aggregate concrete (PLAC) [1]. When the pre-wet pumice replaces the coarse aggregate by 30~40%, the PLAC processed has the advantages of low density, good compressive strength, split tensile strength, and flexural strength, which obviously improves the dynamic performance of the interfacial transition zone (ITZ) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Although improving cement manufacturing technologies can help to reduce emissions [ 4 ], studies have increasingly shown that using alternative materials might be a more accessible and sustainable approach [ 2 ]. Therefore, with the proposal of the new concept of national green development of China and the increasing focus on simultaneously achieving both healthy living environments and development, green building materials are becoming more widespread in their use, especially solid waste produces such as blast furnace slag (BFS) and fly ash (FA), which are used as partial replacements to Portland cement [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such a restriction is also reported for fly ash use in some countries [ 9 , 10 ]. Therefore, the exploration of alternative SCMs and their appropriate use in blended binders is becoming increasingly important, especially those that improve durability properties such as chloride penetration resistance [ 11 ]. However, in the present paper, combinations of CEM I and different, actually available SCMs and fillers are presented in order to achieve a significant CO 2 -reduction in construction practice already today.…”
Section: Introductionmentioning
confidence: 99%